PLGA-based biodegradable microspheres in drug delivery: recent advances in research and application. (1st January 2021) - Su, Yue; Zhang, Bolun; Sun, Ruowei; Liu, Wenfang; Zhu, Qubo; Zhang, Xun; Wang, Rongrong; Chen, Chuanpin
Abstract: Biodegradable microspheres have been widely used in the field of medicine due to their ability to deliver drug molecules of various properties through multiple pathways and their advantages of low dose and low side effects. Poly (lactic-co-glycolic acid) copolymer (PLGA) is one of the most widely used biodegradable material currently and has good biocompatibility. In application, PLGA with a specific monomer ratio (lactic acid and glycolic acid) can be selected according to the properties of drug molecules and the requirements of the drug release rate. PLGA-based biodegradable microspheres have been studied in the field of drug delivery, including the delivery of various anticancer drugs, protein or peptide drugs, bacterial or viral DNA, etc. This review describes the basic knowledge and current situation of PLGA biodegradable microspheres and discusses the selection of PLGA polymer materials. Then, the preparation methods of PLGA microspheres are introduced, including emulsification, microfluidic technology, electrospray, and spray drying. Finally, this review summarizes the application of PLGA microspheres in drug delivery and the treatment of pulmonary and ocular-related diseases.